Carbonation of surface protected concrete - Aguiar, J. L. Barroso de (2013)
Concrete structures are exposed to carbonation that may cause rapid decay, shortening their service life and raising maintenance and repair costs. Carbonation lowers the alkalinity of the concrete depassivating the steel reinforcement. Two limit states can be identified with regard to service life. The first limit state ends when the steel is depassivated. The second limit state is based on cracking of the concrete cover due to oxides generated during corrosion. The service life includes a certain propagation period of corrosion during which the cross-sectional area of steel is progressively decreased, the bond between steel and concrete is reduced and the effective cross-sectional area of concrete is diminished due to spalling of the cover. Surface treatment is commonly used to improve the resistance of concrete to carbonation. A barrier is formed retarding the carbonation reactions in the interior of the concrete. In this study surface protected concretes were compared with non-protected concretes. The used surface protected concretes presented generally lower carbonation diffusion coefficients than the non-protected concretes. The use of epoxy resin showed better protection than the use of acrylic and siloxane resins. The composition of the concretes is an important factor affecting the diffusion of carbonation. The influence of the water–cement ratio was very important. The carbonation diffusion coefficients increased with the water–cement ratio. The prescriptive methodology is not a guarantee to obtain the desired service lives of 50 or 100 years. The desired services lives were only obtained with the use of surface protection treatments.